2014
DOI: 10.1002/mas.21445
|View full text |Cite
|
Sign up to set email alerts
|

HILIC‐MS for metabolomics: An attractive and complementary approach to RPLC‐MS

Abstract: Hydrophilic interaction chromatography (HILIC) is an emerging separation mode of liquid chromatography (LC). Using highly hydrophilic stationary phases capable of retaining polar/ionic metabolites, and accompany with high organic content mobile phase that offer readily compatibility with mass spectrometry (MS) has made HILIC an attractive complementary tool to the widely used reverse-phase (RP) chromatographic separations in metabolomic studies. The combination of HILIC and RPLC coupled with an MS detector exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(122 citation statements)
references
References 129 publications
(137 reference statements)
0
119
0
3
Order By: Relevance
“…The choice of the stationary phase is, therefore, the one that is most‐suited for the broad separation and selectivity of the analytes' physicochemical properties—the most common is reversed‐phase liquid chromatography (RPLC) due to its separation efficiency, versatility, and feasibility, to resolve a large variety of organic compounds . Although C 18 RPLC columns have dominated metabolomics studies, hydrophilic interaction liquid chromatograph (HILIC) has been the alternative choice for stationary phase for polar and hydrophilic metabolites, in particular where biological samples contain a plethora of water‐soluble, polar, and ionic (amino acids, nucleosides, organic acids, sulfates, sugars, vitamins, etc) compounds; the main issue with RPLC is the poor retention of such compounds. Snyder's group showed how the combination of HILIC and RPLC can expand the urine and plasma metabolome by 44% and 108% new metabolic features over RPLC alone .…”
Section: Metabolome Coverage Expansionmentioning
confidence: 99%
“…The choice of the stationary phase is, therefore, the one that is most‐suited for the broad separation and selectivity of the analytes' physicochemical properties—the most common is reversed‐phase liquid chromatography (RPLC) due to its separation efficiency, versatility, and feasibility, to resolve a large variety of organic compounds . Although C 18 RPLC columns have dominated metabolomics studies, hydrophilic interaction liquid chromatograph (HILIC) has been the alternative choice for stationary phase for polar and hydrophilic metabolites, in particular where biological samples contain a plethora of water‐soluble, polar, and ionic (amino acids, nucleosides, organic acids, sulfates, sugars, vitamins, etc) compounds; the main issue with RPLC is the poor retention of such compounds. Snyder's group showed how the combination of HILIC and RPLC can expand the urine and plasma metabolome by 44% and 108% new metabolic features over RPLC alone .…”
Section: Metabolome Coverage Expansionmentioning
confidence: 99%
“…Reversed phase liquid chromatography (RPLC) is the most popularly used separation method1819. However, polar and ionic metabolites, such as organic acids and amino acids, are not suitable to analyze with RPLC because they exhibit low hydrophobicity, which leads to weak interaction with stationary phase, poor retention and separation in RPLC mode1937. Hydrophilic liquid interaction chromatography (HILIC) has been demonstrated to be a preferable technique for the chromatographic retention and separation of polar compounds3839.…”
mentioning
confidence: 99%
“…Compared with RPLC, HILIC methods are suspected to show extended reequilibration times and retention time drifts that cannot (yet) be modeled adequately [34,56]. We have observed that reequilibration of 8 to 10 column volumes between sample injections is sufficient to achieve adequate analytical reproducibility provided that appropriate initial column equilibration was performed (50 column volumes).…”
Section: Discussionmentioning
confidence: 81%